Physical characterization of a soil under management practices in a ’Baianinha’ orange orchard - Cintra, Fernando Luiz Dultra; Coelho, Ygor da Silva; Sobrinho, Almir Pinto da Cunha; Passos, Orlando Sampaio (Pesquisa Agropecuaria Brasileira, 2014)
Sixteen years after planting an experiment with 'Baianinha' orange Citrus sinensis (L.) Osbeck, the physical characterization of the soil submitted to five management practices was done. The practices which were tested included chemical control with herbicide, harrow in the summer plus a grass mower in the winter, continuous harrow and continuous grass mower. The physical determinations made were apparent density, particle density, distribution and size of aggregates, percentage of aggregation, distribution of particles size, water infiltration rata and resistance to penetration. The treatment with continuous grass mower kept the physical characteristics of the soil upgrading its structure due to an increase in organic matter. Continuous harrow led to reduction of aggregate size and percentage of aggregation, and contributed to the formation of a compact layer 10 - 15 cm deep. The use of herbicide promoted the formation of superficial crusts changing the physical properties of the soil decreasing the velocity of water infiltration.